Infanticide in early modern England: the Court of Great Sessions at Chester, 1650-1800 - Dickinson, Roger (Infanticide, 2002)
The murder of new-born children was a phenomenon which attracted considerable comment in early modern England. A year or two before the important 1624 infanticide statute, the clergyman and moralist William Gouge, in his large treatise on family life, described infanticidal mothers as 'lewd and unnatural'.Two years after the statute was passed, the Cheshire justice of the peace Sir Richard Grosvenor described infanticide as 'a sinne which cries for vengeance and rather then it shalbe undiscovered God will worke miracles'. Occasional evidence of community disquiet can be added to such statements by educated or elite commentators. Thus in 1645 a number of the inhabitants of Terling in Essex, headed by their godly minister, petitioned the county bench about an infanticide carried out by Elizabeth Codwell, which they described as an 'unnaturall and barbarous murther ... the guilt whereof we are anxious not to contract', expressing their hopes that 'so horrid a crime may not escape the hand of justice'. There would therefore seem to be considerable justification for Keith Wrightson's commenting on 'the enormous symbolic significance which infanticide had acquired in European culture' by the early modern period, and the way in which it 'had been identified as an unnatural act'. Certainly, the offence is now regarded by historians of early modern crime as one of the distinctive offences of the period. Most European states enacted legislation which defined infanticide as a separate offence, which became one of the more salient forms of female criminality in the early modern period. Infanticide was a more sex-specific crime than witchcraft, that other offence so closely associated 36with women, and it is probable that what might be termed an 'infanticide craze' in early modern Europe led to the execution of at least as many women as did the more familiar European witch-craze.